Supply Chain Resilience in the Context of Global Production and Logistics - Ghani, Jaharah; Abdollah, Mohd Fadzli; Rizal, Muhammad; Juri, Afifah Zakiyyah; Elias, Sulaiman; Abdul Rashid, Aizat; Kamaruzaman, Qamarul Syahmi; Zainudin, Nur Ain Najwa; Hairil Azmi, Muhammad Nursyakirn (Al-Khwarizmi Engineering Journal, 2025)
This paper presents an in-depth review of supply chain resilience in the context of global production and logistics, considering the immediate need for adaptive and robust systems in the growing global scenario of uncertainties. This study aims to investigate the needs and strategy of SCR for global production and logistics. First, 39 articles focusing on SCR in the context of global production and logistics are selected. The articles are then classified according to the resilience strategy proposed by the authors. From the selected works published, the study unravels the key themes, such as definitions of resilience, disruption drivers, integration of digital technologies (e.g. digital twins) and the importance of cybersecurity. The paper further discusses the drawbacks of lean manufacturing, resilience metrics and its industrial applications during momentous events such as COVID-19. The findings demonstrate that although applications of technology, such as AI and predictive analytics, have reinforced the resilience of production planning and control, many issues remain unaddressed in terms of the standardisation of metrics and coordinating sustainability with resilience. The paper presents recommendations endorsing hybrid resilience-efficiency models, cyber-resilience frameworks and multi-industry strategies to enable supply chains to face future disruptions.